The Role of Technology Usage Interest in Mediating the Effect of Selena Application Service Features on Job Satisfaction : A Study on Sales Personnel of PT Pegadaian Regional Office VII Denpasar - Ni Ketut Yunita Indrawati; I Gede Riana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the influence of the Selena application’s service features on job satisfaction among sales personnel at PT Pegadaian Kanwil VII Denpasar, with the interest in using technology serving as a mediating variable. The research is motivated by the growing importance of digital applications in supporting operational performance and employee satisfaction, especially in the financial services sector. A quantitative causal research approach was employed to examine the relationships between the variables. Data were obtained through questionnaires distributed to respondents and supplemented with interviews to gain deeper insights. The sample consisted of 50 active sales personnel operating in the Bali region, selected using purposive sampling to ensure relevance to the research objectives. Data analysis was carried out using Structural Equation Modeling with the Partial Least Square (SEM-PLS) method through the WarpPLS 8.0 application. This analytical approach was chosen because it is effective in testing complex causal relationships and mediation effects, even with relatively small sample sizes. The findings reveal that the service features of the Selena application have a positive and significant effect on job satisfaction. Furthermore, the service features also exert a positive and significant influence on employees’ interest in using technology. The interest in using technology itself positively and significantly affects job satisfaction, confirming its role as an important factor in enhancing workplace outcomes. In addition, the mediation test results demonstrate that the interest in using technology significantly mediates the effect of service features on job satisfaction. These results highlight the importance of continuously improving application service features and fostering employees’ willingness to adopt technology to maximize job satisfaction and overall performance.